Response of Chromolaena odorata to different tree densities in a tropical agrisilvicultural system. Aboveground biomass production, partitioning, decomposition and nutrient release - Norgrove, L.; Hauser, S.; Weise, Stephan F. (Elsevier, 2000)
In low-input land-use systems combining timber trees with shade-tolerant understorey crops, it is essential to establish the effects of tree density upon weeds and the contribution of weeds to competition and nutrient cycling. Adjusting tree density may alter weed competition for light, water and nutrients, the storage of nutrients by weeds through growth and the release of nutrients via decomposition of slashed weed residues. The effects are reported of (1) two timber stand densities (TSDs) and, (2) retention versus burning of slashed vegetation at field preparation, upon Chromolaena odorata (kondengui), the dominant weed, in an agrisilvicultural system in southern Cameroon. The system comprised the timber species, Terminalia ivorensis, and plantain as an understorey crop. Total weed biomass was measured at the first weeding, 3 months after planting (MAP), and total weed biomass and aboveground biomass, partitioning and nutrient accumulation of C. odorata were measured at the second and third weedings, 7 and 12 MAP. Mass and nutrient loss were measured from stem and leaves placed separately in decomposition bags. Here, burning was not an appropriate weed management tool, as it resulted in greater weed biomass. A high TSD did reduce weed biomass. However, foliar nutrient concentrations were generally higher in high TSDs. Thus, retaining trees in the high TSD did not lead to any reduction in nutrient uptake by the C. odorata stand. Furthermore, in the high TSD, mass loss and nutrient release characteristics had higher coefficients, and a higher percentage of the total nutrients accumulated were released in the early stages of incubation, all increasing the risk of nutrients being lost from the topsoil. Thus, from a weed competition perspective, there were few benefits to retaining a high timber stand density.